Field Evidence for the Initiation of Isolated Aeolian Sand Patches. Issue 4 (13th February 2023) - Delorme, P.; Nield, J. M.; Wiggs, G. F. S.; Baddock, M. C.; Bristow, N. R.; Best, J. L.; Christensen, K. T.; Claudin, P.
Abstract: Sand patches are one of the precursors to early stage protodunes and occur widely in both desert and coastal aeolian environments. Here we show field evidence of a mechanism to explain the initiation of sand patches on non‐erodible surfaces, such as desert gravels and moist beaches. Changes in sand transport dynamics, directly associated with the height of the saltation layer and variable transport law, observed at the boundary between non‐erodible and erodible surfaces lead to sand deposition on the erodible surface. This explains how sand patches can form on surfaces with limited sand availability where linear stability of dune theory does not apply. This new mechanism is supported by field observations that evidence both the change in transport rate over different surfaces and in situ patch formation that leads to modification of transport dynamics at the surface boundary. Plain Language Summary: Sand patches can be observed in various environments such as beaches and gravel plains in deserts. Expected to be precursors of dunes when sediment supply is limited, these bedforms are typically a few centimeters high and present a reverse longitudinal elevation profile, with a sharp upwind edge and a smooth downwind tail. Based on field measurements, we propose a formation mechanism for these patches associated with the sensitive nature of wind‐blown sand transport to changing bed conditions: sand saltation is reduced at the transition from a solid to an erodible surface, hence favoring deposition on the patches. This allows us to explain their typical meter‐scale length as well as their asymmetric shapes. Key Points: Sand patches can emerge on non‐erodible surfaces Differing surfaces characteristics control particle behavior Field measurements demonstrate the key role of sand transport in bedform initiation